Immunoprophylaxis of Respiratory Syncytial Virus Infection in Children - A. A. Baranov; L. S. Namazova-Baranova; I. V. Davydova; E. L. Bokeriya; E. A. Vishnyova; M. V. Fedoseyenko; L. R. Selimzyanova (Union of pediatricians of Russia, 2015)
The article is dedicated is to the issue of respiratory syncytial virus (RSV) infection in children. Urgency of this issue is beyond any doubt. RSV prevalence in the children hospitalized due to infections of lower airways is 18-33% in the advanced countries; up to 30% of the population become infected in the seasonal period of morbidity rise; 70% of children undergo RSV infection in the first year of life; almost every child becomes infected within the first two years of life. Infants are characterized by severe course of RSV infection; the most commonly hospitalized age group is infants aged 2-5 months. Especially severe and life-threatening course is observed in premature infants and young children with immature and/or pathological cardiorespiratory system - in patients with congenital malformations and immunodeficiencies. Specialists of the professional association of pediatricians "Union of Pediatricians of Russia" formulated and briefly described the main peculiarities of RSV infection and characterized groups of severe course risk, as well as indications and patterns of passive immunization - the only reliably effective preventive technology available at the moment, which allows preventing incapacitating consequences of RSV infection - in accordance with principles of the evidence based medicine.